Data from: Evidence for nonconsumptive effects from a large predator in an ungulate prey? ... - Gehr, Benedikt; Hofer, Elizabeth J.; Ryser, Andreas; Vimercati, Eric; Vogt, Kristina; Keller, Lukas F. (Dryad, 2018)
Pedators can indirectly affect prey survival and reproduction by evoking costly anti-predator responses. Such non-consumptive effects may be as strong or stronger than consumptive predator effects. However, evidence for this in large terrestrial vertebrate systems is equivocal and few studies quantify the actual fitness costs of non-consumptive effects. Here we investigated whether non-consumptive effects elicited by Eurasian lynx (Lynx lynx), a large terrestrial predator, reduced survival in an ungulate prey, the European roe deer (Capreolus capreolus). To reveal the behavioral processes underlying non-consumptive effects, we distinguished between proactive risk avoidance of areas with high lynx encounter probability, and reactive risk avoidance in response to actual lynx encounters and analyzed these responses using step selection functions. We also quantified the consequences of these behaviors for deer survival. Deer reacted differently at day and at night, but avoided high-risk areas proactively during ... : DeerDayDataDeerNightDataLynxDataDeerMortalityDataThis table contains the mortality data of 65 collared deer used to build the cox proportional hazard model in Gehr et al. 2018 (Behavioral Ecology). The column nr_days refers to the number of days a deer was monitored whereas entry_day and exit_day refer to the day the animal entered or left the study relative to the starting date of the study (30 November 2011). Fate refers to the fate of the animal (1 indicates died of non-lynx related causes, 0 indicates either alive at the end of monitoring or killed by lynx). Mort_cause refers to the cause of mortality. The code for mortalities: 2=disease/starvation, 3=road kill, 6=lynx kill, 7=dog kill, 10=hunting, 11=unknown. Human_risk refers to the mean human disturbance index value for all locations for each deer (composite of house density and distance to the closes road). Mean alti refers to the mean altitude of all locations for each deer. Mean_pr refers to the mean predation risk value (based on a lynx resource ...